Choice of treatments of the coronal shear fractures of the humerus. A national survey of Italian AO members. (March 2023) - Vicenti, Giovanni; Bizzoca, Davide; Zaccari, Domenico; Buono, Claudio; Carlet, Arianna; Solarino, Giuseppe; Giorgino, Riccardo; Santolini, Emmanuele; Lunini, Enricomaria; Zavattini, Giacomo; Ottaviani, Guglielmo; Carrozzo, Massimiliano; et al.
Abstract: Introduction: Coronal shear fractures of the distal humerus are uncommon injuries representing 6% of distal humeral fractures. There is no univocal consensus about the correct management of this type of fracture. A national survey was conducted to gain more insight into the current classification, diagnosis and treatment of coronal shear fractures in Italy. Materials and methods: A postal survey was sent to all AO Italian members including residency orthopaedic surgeons. The survey consisted of general questions about personal experience in the management of these fractures: types of classification systems used, surgical approaches, treatment options and rehabilitation programs. Results: 114 orthopaedic surgeons answered a 13-items questionnaire. The most used classification system was AO/OTA (72, 8%). Independent screws and if necessary plates were the most answered regarding surgical treatment (81, 6%). The most encountered post-surgical complication was stiffening of the elbow (81, 6%). Conclusion: An algorithm of treatment has been proposed. To better classify coronal shear fractures, the authors recommended the integration of two classification systems: AO and Dubberley classifications. In the case of posterior wall comminution, a Kocher extensile approach is recommended, otherwise, if a posterior wall is intact, Kocher or Kaplan approach can be used. The posterior transolecranic approach can be reserved to Dubberley type III or AO 13B3.3. The best treatment choice is represented by independent screws and plates placed according to fracture patterns while arthroplasty is indicated when a stable ORIF is not possible. Mobilization is postponed for about 2 weeks.